Message strategy in short film production competition for strengthening film ecosystem - Arindi, Citra; Abdullah, Aceng; Arifin, Hadi Suprapto (Universitas Padjadjaran, 2023)
Background: Film festivals in Indonesia are mostly used by filmmakers as a premiere space and showcase their work. The pandemic delayed the festival, which was not even held then, while film production was delayed. The Film, Music, and Media Directorate organize a Short Film Production Competition to strengthen the film ecosystem. A communication strategy must convey information to match the community’s expectations and the program’s objectives. Purpose: Therefore, this study aims to analyze the competition’s message orientation and message style. Methods: This research uses qualitative methodology with a case study approach based on Kotler’s marketing management and Joep Cornelissen’s message strategy model. Researchers obtained preliminary data from publication content with the highest number of ‘Likes’ on Instagram @pusbangfilm, then classified based on the series of activities of this competition to get an overview of the message strategy. Results: This research shows results that Hashtags, Colors, Fonts, and other visual elements emotionally attract attention the first time. Choosing words, language, and who conveys it becomes a stronger attraction. It is necessary to bring added value from the program, for example, with Behind the Scene content. Positive testimonials from various parties are also important messages conveyed. The general description of the program and the purpose of the program influenced the determination of the message theme so that it adjusted message orientation and in what style conveyed the message to stakeholders. Implication: Competition or festival organizers design messages following the objectives to be achieved from organizing the festival or competition.